Komunikasi Ketua RW 010 Kelurahan Kaliabang Tengah Kepada Masyarakat Dalam Proses Pengembangan Program Bekasi Smart City - Annisa Eka Syafrina (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The relatively fast population growth in urban areas causes various problems such as a decrease in the quality of public services, reduced availability of residential land, congestion on highways, difficulty in getting parking spaces, increased crime rates and other social problems. These problems will continue to increase as the population increases and cannot be solved quickly and precisely. Therefore, smart solutions are needed so that solving these problems can be done faster than the growth of the problem itself, one of which is the application of city ecosystem collaboration in the Smart City concept. Bekasi City, is one of the cities that received assistance from the central government to participate in the Movement Towards 100 Smart Cities in Indonesia. The public's understanding of the existence of Bekasi Smart City is not yet known in its entirety, both in the fields of industry, education, services, and others. Therefore, it is necessary to provide counseling and publications to make people aware that this is an important step in overcoming various urban problems. This study aims to find out how the communication carried out by the Chairperson of RW 010, Kaliabang Tengah Village to the community in the process of developing the Bekasi Smart City program. By using qualitative research methods with descriptive types, researchers conducted interviews with informants related to the research. The results of the study indicate that the communication made by the RW leader to its citizens meets the element of openness, which is one of the requirements for an effective interpersonal communicator to be open to the people he invites to interact with, empathy, supportive attitude, support. positive attitude, and equality. Keywords : Bekasi, Communication, Urban, Smart City